2021
DOI: 10.1021/acsami.1c16151
|View full text |Cite
|
Sign up to set email alerts
|

Tetrahedral Framework Nucleic Acids Reverse New-Onset Type 1 Diabetes

Abstract: Type 1 diabetes (T1D) is caused by breakdowns of central and peripheral immune tolerance and destructions of insulin-producing β-cells. Conventional insulin injection cannot cure the disease. Regulatory immune cells, including regulatory T-cells (Tregs) and regulatory B-cells (Bregs), play critical roles in immune tolerance. Inducing regulatory immune cells to halt the progress of T1D and restore immune tolerance is the promising approach in T1D immunotherapy. Here, tetrahedral framework nucleic acids (tFNAs) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 67 publications
1
7
0
Order By: Relevance
“…Here an 8% polyacrylamide gel electrophoresis (PAGE) was used to illustrate that tFNAs were successfully synthesized (Figure b). The molecular mass of tFNAs was shown to be around 200 base pairs (bp) using marker as a reference, consistent with our former findings. , TEM was employed to demonstrate the shape of tFNAs, resembling a triangle on a two-dimensional scale (Figure c). The ζ-potential result of tFNAs showed a negative surface charge of 6.967 ± 1.207 mV (Figure d), and dynamic light scattering showed that the average size of tFNAs was approximately 10 nm (Figure e).…”
Section: Synthesis and Characterization Of Tfnassupporting
confidence: 85%
See 1 more Smart Citation
“…Here an 8% polyacrylamide gel electrophoresis (PAGE) was used to illustrate that tFNAs were successfully synthesized (Figure b). The molecular mass of tFNAs was shown to be around 200 base pairs (bp) using marker as a reference, consistent with our former findings. , TEM was employed to demonstrate the shape of tFNAs, resembling a triangle on a two-dimensional scale (Figure c). The ζ-potential result of tFNAs showed a negative surface charge of 6.967 ± 1.207 mV (Figure d), and dynamic light scattering showed that the average size of tFNAs was approximately 10 nm (Figure e).…”
Section: Synthesis and Characterization Of Tfnassupporting
confidence: 85%
“…Recent accumulating evidence has indicated that tFNAs possessed a strong capacity in regulating cellular biological behaviors including proliferation, migration, apoptosis, and autophagy. tFNAs were also proved to possess extraordinary anti-inflammatory and antiapoptotic capability in former studies and were utilized in animal models to treat a wide variety of diseases. According to our previous studies, tFNAs were used to tackle acute kidney injury (AKI) and showed remarkable capacity in rescuing kidney tissue, according to the significant changes observed in various parameters of renal function . Mi Zhou and others in 2020 also proved that tFNAs treatment could alleviate inflammation both in vitro and in model animals with periodontitis, a well-recognized leading cause for tooth loss worldwide …”
Section: Synthesis and Characterization Of Tfnasmentioning
confidence: 99%
“…Experiments were carried out as described above. , See the Supporting Information for the specific experimental methods.…”
Section: Methodsmentioning
confidence: 99%
“…Apart from cancer treatments, the potential of DNA nanostructures in the treatment of other diseases (e. g., inflammatory and degenerative diseases) has also been extensively explored. In recent years, Lin′s research group has designed a series of tetrahedral frame nucleic acids (tFNA)‐based DNA nanostructures for treatment of different diseases, including new‐onset type 1 diabetes, [109] acute gouty arthritis, [110] intracranial hemorrhage, [111] demyelinating diseases, [112] and so on, achieving remarkably therapeutic effects [113] . Notably, they found tFNA has the intrinsic ability to prevent neuronal apoptosis via blocking the TLR2‐MyD88‐NF‐κB signaling pathway, which could efficiently alleviate the acute ischemic stroke [114] …”
Section: Therapeutic Applicationmentioning
confidence: 99%